Interactions between Shigella flexneri and the Autophagy Machinery - Krokowski, Sina; Mostowy, Serge (Frontiers in Cellular and Infection Microbiology, 2016)
Autophagy, an intracellular degradation process, is increasingly recognized as having important roles in host defense. Interactions between Shigella flexneri and the autophagy machinery were first discovered in 2005. Since then, work has shown that multiple autophagy pathways are triggered by S. flexneri, and autophagic responses can have different roles during Shigella infection. Here, we review the interactions between S. flexneri and the autophagy machinery, highlighting that studies using Shigella can reveal the breadth of autophagic responses available to the host.